Approximate Euler-Lagrange Quadratic Mappings in Fuzzy Banach Spaces - Hark-Mahn Kim; Juri Lee (Abstract and Applied Analysis)
We consider general solution and the generalized Hyers-Ulam stability of an Euler-Lagrange quadratic functional equation in fuzzy Banach spaces, where , are nonzero rational numbers with , .